Time-series models of sea lice Caligus elongatus (Nordmann) abundance on Atlantic salmon Salmo Salar L. in Loch Sunart, Scotland - McKenzie, Eddie; Gettinby, George; McCart, Kevin; Revie, Crawford W. (Aquaculture Research, 2004)
Most lice infestations on salmon farmed in the North Atlantic are attributed to Caligus elongatus and Lepeophtheirus salmonis. This study reports findings from time-series analysis conducted on observations of the lesser-studied C. elongatus, in four farms on the west coast of Scotland over the period 1996-2000. Least-squares and Poisson regression techniques were applied to one individual site and to the aggregated data of four sites. Models were fitted and tested for goodness of fit using appropriate statistical methods. Findings indicate that infestation levels are highly seasonal with rapidly increasing numbers after week 22 of the year followed by a steady decline from week 40. Abundance is much lower in the second year of the production cycle than the first. Neither of the models indicated that treatment application has a significant effect on C. elongatus infestations.